2015
DOI: 10.1007/s11250-015-0954-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the microscopic agglutination test seroepidemiology of bovine leptospirosis in Latin America

Abstract: The diagnosis of leptospirosis commonly relies on serology, which has three issues that are referred: the sampling, the antigen panel, and the cutoff point. We propose a systematic review of the bovine leptospirosis in Latin America, in order to provide a better understanding of the evolution of the research and of the seroepidemiology of bovine leptospirosis in that region. Internet databases were consulted over the year of 2014. Inclusion criteria for analysis included serosurvey using microscopic agglutinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 56 publications
4
20
3
Order By: Relevance
“…Therefore, it is necessary to execute other studies by using isolation and molecular techniques to investigate the importance of this serogroup as a cause of abortion in buffalo. Pinto et al 18 (245) reinforce the necessity of studies in different countries and a greater standardization of the diagnosis of Leptospira spp. infection.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, it is necessary to execute other studies by using isolation and molecular techniques to investigate the importance of this serogroup as a cause of abortion in buffalo. Pinto et al 18 (245) reinforce the necessity of studies in different countries and a greater standardization of the diagnosis of Leptospira spp. infection.…”
Section: Discussionmentioning
confidence: 95%
“…17 Otherwise, a comparison between the results obtained in different studies is difficult to analyze, because the MAT technique may vary among laboratories according to their collection of antigens. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, MAT titration against Canicola was only found in two dogs, which had low titers against this serogroup. Canicola strains are frequently isolated from dogs in Brazil and other locations [ 15 , 16 , 37 ], although serological evidence of Canicola infection is not often observed [ 38 ]. A previous study including dogs suspected of clinical leptospirosis conducted by our group between 2008 and 2012 found that even though most dogs reacted against serogroup Icterohaemorrhagiae, Canicola strains could still be recovered from three symptomatic dogs which had no MAT titers against this serovar [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptospiral strains are broadly distributed in soil and water worldwide. As described by Bharti et al, the group of natural reservoirs of pathogenic leptospires is vast and continues to increase [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%